OP30 Social participation and ischaemic heart disease incidence and mortality in middle-aged women: a prospective cohort study. (2nd September 2014) - Floud, S; Balkwill, A; Canoy, D; Reeves, GK; Green, J; Beral, V; Cairns, BJ
Abstract : Background: Participation in social activities has been associated with lower all-cause and vascular mortality and there is some evidence of a lower risk of first ischaemic heart disease (IHD) events. However these associations could be due to reverse causation, whereby good health determines participation rather than the other way around, or they could be confounded by lifestyle factors. There is also a lack of evidence on whether participation in specific types of social activity is associated with a lower risk of IHD. We examined the association between social participation and ischaemic heart disease incidence and mortality in the Million Women Study. Methods: A total of 735, 159 women (mean age 60 years), without heart disease, stroke or cancer, reported participation in 8 different types of activity: religious groups, voluntary work, adult education, art/craft/music, dancing, sports club, yoga and bingo. We used Cox regression to estimate adjusted relative risks (RRs) and 99% confidence intervals (CIs) of first IHD events and IHD mortality by participation and in various types of social activity. Results: Nearly two-thirds (59%) of the women reported that they took part in at least one social activity. During 8.7 years of follow-up, 30, 756 women had a first IHD event and overall 2150 women died from IHD. Women who participated in activities tended to be of a higher socio-economic position and have fewer risk factors for IHD. After adjustment for socio-demographic and lifestyle factors, there was little difference in risk of a first IHD event for women who participated in social activities compared to those who did not (RR=1.01, 99% CI 0.98–1.04), but there was a lower risk of IHD mortality (RR=0.81, 99% CI 0.72–0.91). There was only a slight attenuation in the risk estimates when the first four years of follow-up were excluded to investigate potential for reverse causation. However, the direction of the association varied by type of activity, with higher risks associated with bingo and lower risks associated with the other social activities. Conclusions: Women who participated in social activities were not at a lower risk of having a first IHD event but were at a lower risk of death from IHD. However, the lower risk of death was not found for all activities, suggesting that the association between social participation and death from IHD may reflect other aspects of the lifestyles of these women.